The Economic Policy Uncertainty and Firm Investment in Germany - Oliver, John (Journal of Accounting, Business and Finance Research, 2020)
The importance of the impact created by different uncertainties in the policies on the overall economy of a country or a region cannot be denied. These uncertainties might be because of political reasons but sometimes the overall economic environment brings such uncertainties as well. Being a crucial part of economy of the country, German firms might face different issues because of these uncertainties. In this regard, the researcher conducted this study with the motive to find the influence that EPU has on the investments made by various firms of Germany and for this purpose, the researcher derived data from the non-financial companies regarding their finance activities on quarterly basis for the time span consisting of 20 years. SYS GMM estimation was applied on the gathered data to fulfil the purpose of the study. The major result showed that EPU has important but negative impact on the investments made by the German firms. The next result that involves the heterogeneity impact of the firms show that although EFU alone has negative or declining impact on investments but when it is incorporated with the heterogeneity variables of the firm, the impact of these interactions become positive on the firms’ investments. The last result including marketization is that when the marketization index interacts with EPU, the impact of EPU is more sensitive in case of highly marketed companies as compared to lower ones. The study has suggested that the policymakers must make transparent and favorable policies for the firms in regard of investments.